Utilizing Cartoon Movie Media to Improve Listening Skill of IV Graders Elementary School SDN Prambontergayang 2 - Jepri Perdana Aditya (JPP (Jurnal Pendidikan dan Pembelajaran), 2018)
This research intends to examine the listening skill of IV Graders of elementary school at SDK Wololanu after learning with cartoon film media. This research was a classroom action research (commonly referred to as CAR). It employed Kemmis and Taggart research model and used qualitative approach. The data were obtained by using test, observation, field notes, and documentation. The results show that cartoon film media improves listening skills of students.